Stepwise interview with private sector - Olam (U) Ltd - Mr. Jeremy Dufour - Margiotta, S. (International Institute of Tropical Agriculture, 2019)
Interview with the sustainability manager, Olam international who talks about their sustainability approach and strategy. he also highlights the benefits of working with research organisation like IITA in implementing the stepwise approach and in providing practical and scalable solutions that are scientific tested and Olam future prospects.